Exploring the Relational Impact of Service Quality on Customer Satisfication - Yadav, Manish Kumar; Rai, Dr. Alok Kumar (Ushus Journal of Business Management, 2021)
Customer Satisfaction has been a psychological attribute inviting attention of the customers and requiring decipher their contribution in overall business performance.Banking has been no exception to this phenomenon.Many Literatures have found a strong relationship between service quality and customer satisfaction In service sector in general and banking industry in particular. The aim of the study is to investigate the relationship between service quality and customer satisfaction. The study assesses the level of customers’ satisfaction and service quality performance of the select banks. Further the study compares the satisfaction and service quality in select public and private sector banks.The study also identifies the area where the banks need to focus. The research design is descriptive as the research is intended to conclude and suggest measures to zero down on the service quality gaps in select public and private sector banks. The result shows a positive relationship between service quality and customer satisfaction. Service quality dimensions (tangibility, reliability, responsiveness, assurance and empathy) show wide service quality gaps. The comparative study of public sector banks and private sector banks show superiority of private sector banks over public sector banks in customer satisfaction and performance of service delivery.